Vivir la gracia de Dios : un compromiso social metodista permanente : contribuciones para la identidad del metodismo peruano - Salazar, Rebeca Soledad Luza (2007)
Living the Grace of God: A permanent Methodist social commitment. Contributions to the identity of Peruvian Methodism. The first part addresses the manifestation of God s Grace in Wesleyan theology, its core aspects and the way Grace delineates Methodist identity. The second part deals with the question of what characterizes the Methodist identity marked by charitable deeds and works of mercy, and the way these, as means of Grace and external signs, are provided by God for our own and our community s spiritual formation. Another characteristic that is also addressed in this part is the evangelizing spirit as a response to the mandate given by our Lord Jesus Christ to go out and preach the Gospel to all creatures. The third part addresses the Methodist presence in Peru. From its origins in the Nineteenth Century with the presence of the British and American Biblical Societies, the sending of Colporteur missionaries; the first attempt to establish the Methodist Mission with William Taylor (1877-1887); the second and final attempt to establish the Methodist work with Francisco Penzotti (1888-1889), the work done by Dr. Thomas B. Wood and the organization of the Methodist Mission, his contribution in the legal and educational fields; the work done by the first Peruvian Methodist ministers such as José Q. Illescas, Manuel Noriega and Adolfo T. Vásquez. The organization of the Missionary Work during the 1904-1939 period, the full expansion and development of the organization during the 1940-1969 period. The church s autonomy in 1970, with the first changes in the structure of the mission up to the holding of the First Constituent Assembly with the election of the first Peruvian bishop, Dr. Wenceslao Bahamonde. The heyday of an autonomous church that learns to walk on its own but not always lives the Grace of God and goes through a crisis of identity and testimony. The last part ends with the Methodist Church s current contribution to the Peruvian society through educational and charitable work, as well as ecumenical commitment and the challenges that we are forced to face, as Christian church, for the transformation of the Peruvian society. Living the Grace of God is a permanent Methodist social commitment and the Methodist Church of Peru is called and challenged to transform the Peruvian society, to share the Grace that it received with those who live in disgrace, those who are denied the Grace of God on a daily basis. Living and sharing the Grace of God today in Peru is a mission that cannot be put off